PENGARUH PSYCHIC REWARD DAN SOCIAL REWARD TERHADAP KEPUASAN KERJA PETUGAS KEBERSIHAN PADA DINAS LINGKUNGAN HIDUP KOTA PAREPARE - Wahyuni, Sri; Sampara, Nirwana (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study aimed to determine the effect of Psychic Reward and Social Reward on the Job Satisfaction of Cleaners at the Dinas Lingkungan Hidup, Kota Parepare. The data collection techniques used in this study are observation, questionnaires, and interviews. The sample in this study amounted to 193 respondents. The data analysis used was descriptive analysis test, data quality test, and multiple linear regression with hypothesis testing, determination test, and t-test. Data management tools using SPSS version 21.0. Based on the results of research that have been complete. It shows that Psychic Reward has a positive and significant effect on the Job Satisfaction of Cleaners at the Dinas Lingkungan Hidup, Kota Parepare. The Social Reward has a positive and significant impact on Job Satisfaction of Cleaners at the Dinas Lingkungan Hidup, Kota Parepare. Psychic Reward and Social Reward have a positive and significant effect on the Job Satisfaction of Cleaners at the Dinas Lingkungan Hidup, Kota Parepare.